Animal Welfare in Extensive Production Systems Is Still an Area of Concern - Temple, Déborah; Manteca, Xavier (Frontiers in Sustainable Food Systems, 2020)
Traditionally, research on farm animal welfare has mainly been focused on welfare problems thought to be common in intensive systems, whereas the welfare of animals kept in extensive systems has attracted much less attention. This may be due to the generally held belief that extensive systems are advantageous in terms of animal welfare. Although it is undeniable that extensive systems have many benefits in terms of animal welfare, they are by no means free of welfare problems. This review highlights the animal welfare problems that are most likely to be found in extensive systems following the four animal welfare domains of “nutrition,” “environment,” “health,” and “behavior.” Extensive environments are highly variable and heterogeneous in terms of climate conditions, food quality, and access to high-quality water, and this can raise serious welfare concerns related to chronic hunger and thirst, and thermal stress. These problems will vary depending on the location and time of year. Some diseases are more likely in extensive systems than in intensive ones and this can be compounded by supervision of animals being more difficult in extensive systems. Several painful husbandry procedures as well as neonatal mortality and predation are other potential welfare issues for animals raised in extensive systems. Finally, infrequent handling and / or potentially aversive handling can impair human-animal relationship and have a negative effect on the welfare of extensive livestock. Detection and monitoring of welfare problems in extensive systems are essential for implementing practical solutions adapted to local challenges. Selecting animals that are adapted to local conditions reduces some of the welfare problems encountered in extensive systems. Practice-led innovations should be undertaken in extensive systems and should support knowledge-exchange strategies with producers.